Changes related to gender, geographic population and habitat in the antennal phenotype of Triatoma patagonica Del Ponte (Hemiptera: Reduviidae) - Rodriguez, Claudia Susana (2013)
Triatomines undergo morphological changes as an adaptive response to different habitats (wild, peridomestic, domestic, laboratory). The characterization of the antennal phenotype provides information on intraspecific variation caused by geographical origin and/or habitat. Triatoma patagonica Del Ponte, 1929 is known to occur in peridomiciles of rural areas in Argentina, where it also invades non-colonized dwellings. Here we describe and compare the antennal phenotype of T. patagonica in populations of different geographic origin, and explore possible modifications induced by laboratory rearing with the aim of investigating the range of phenotypic variation of the species for the first time. Sixty antennas of adult males and females of T. patagonica belonging to two peridomiciliary populations of different geographical origin were analyzed. Four types of sensilla were observed in three antennal segments, showing sexual dimorphism in the species. The multivariate analysis separated the populations of similar habitat (peridomicile) but different geographical origin, without showing differences between the peridomiciliary and laboratory populations of the same geographical origin. These results suggest phenotypic plasticity in T. patagonica, which would allow the species to adapt to a wide range of habitats without having a close association with a given host and its environment. The range of antennal phenotypic variation of T. patagonica would also be an indicator of its current stage of adaptation to the human environment.